New Perspectives in the Noble Gas Chemistry Opened by Electrophilic Anions - Rohdenburg, Markus; Azov, Vladimir A.; Warneke, Jonas (Frontiers in Chemistry, 2020)
Binding of noble gases (NGs) is commonly considered to be the realm of highly reactive electophiles with cationic or at least non-charged character. Herein, we summarize our latest results evidencing that the incorporation of a strongly electrophilic site within a rigid cage-like anionic structure offers several advantages that facilitate the binding of noble gases and stabilize the formed NG adducts. The anionic superelectrophiles investigated by us are based on the closo-dodecaborate dianion scaffold. The record holder [B12(CN)11]- binds spontaneously almost all members of the NG family, including the very inert argon at room temperature and neon at 50 K in the gas phase of mass spectrometers. In this perspective, we summarize the argumentation for the advantages of anionic electrophiles in binding of noble gases and explain them in detail using several examples. Then we discuss the next steps necessary to obtain a comprehensive understanding of the binding properties of electrophilic anions with NGs. Finally, we discuss the perspective to prepare bulk ionic materials containing NG derivatives of the anionic superelectophiles. In particular, we explore the role of counterions using computational methods and discuss the methodology, which may be used for the actual preparation of such salts.